The overview of the Presidential Primary campaign of Bernie Sanders: the analysis of his political background and the influence of celebrity endorsement and social media on voters. - Tomaszewski, Norbert (Political Preferences, 2017)
Bernie Sanders became the phenomenon of this year's Presidential Primary campaign in the Democratic Party. In order to analyse his road to success, I have decided to focus on three main factors, that helped him conquer on an equal level with Hillary Clinton: his political background, the social media activity of his campaign staff and the celebrity endorsement. The aim of this article is to show, how in the 21st century, the role of the traditional media during the campaign is weakened by the influence of the Internet 2.0 tools. The work also focuses on the behaviour of the American voters and what impact does the regular internet use have on them. Key words: Internet 2.0, political marketing, voter behaviour, celebrity endorsement, Democratic Party, social media, political campaigns